2017
DOI: 10.1021/acs.joc.7b02769
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Hetero-Diels–Alder Reaction of Benzocyclobutenones with Isatins To Form 2-Oxindole Spirolactones

Abstract: Benzocyclobutenones 1a–1g undergo cycloreversion at 150 °C in m-xylene solvent to form transient α-oxo-ortho-quinodimethanes or “ortho-quinoid ketene methides,” which engage in intermolecular [4+2] cycloadditions with isatins 2a–2f to form 2-oxindole spirolactones 3a–3l. This process tolerates an array of different functional groups and substitution patterns, and is applicable to unprotected isatins 2b–2f bearing free NH-functionalities. The superior performance of isatins compared to other carbonyl based dien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…9 New entries include cycloaddition reactions of cyclobutenone 320 with imine 321 146 and diazomethane 323, 147 and a cycloaddition reaction of benzocyclobutenone 254 with isatin 325 (Scheme 77). 148 A cycloaddition reaction of 3-aminocyclobutenone 327 with ynoate 328 proceeds through enamine-imine tautomerization of vinyl ketene intermediate 329 (Scheme 78). 149 4-Pyridone 331 is selectively produced through this process.…”
Section: Thermally-induced Ring-openingmentioning
confidence: 99%
“…9 New entries include cycloaddition reactions of cyclobutenone 320 with imine 321 146 and diazomethane 323, 147 and a cycloaddition reaction of benzocyclobutenone 254 with isatin 325 (Scheme 77). 148 A cycloaddition reaction of 3-aminocyclobutenone 327 with ynoate 328 proceeds through enamine-imine tautomerization of vinyl ketene intermediate 329 (Scheme 78). 149 4-Pyridone 331 is selectively produced through this process.…”
Section: Thermally-induced Ring-openingmentioning
confidence: 99%
“…Under these conditions, 3 a was obtained in 94 % NMR yield and only 3 % of 3 a' was detected in the crude reaction mixture. Although a few examples of the C1 À C8 bond cleavage of BCBs has been reported by heating at high temperature through retro-4p cyclization, [23] the [4+2] cycloaddition of BCBs with unactivated alkynes has not been realized. Indeed, control experiments showed that no desired reaction occurred in the absence of nickel catalyst, precluding the possibility of thermal cycloaddition pathway (Table 1, entry 1).…”
mentioning
confidence: 99%
“…As part of our ongoing research interest in the development of novel methodologies, particularly the hetero-Diels-Alder reactions of o-quinodimethanes (o-QDM), 8 for the preparation of heterocycles, we foresee that the exploitation of sultines as masked o-QDMs 9,10 in an oxa-Diels-Alder (oxa-DA) reaction could serve as an alternative means to directly access functionalized isochromans. The reactivity of the highly reactive o-QDMs in an oxa-DA has been previously established by Glorius, 11 Chi, 12 Yao, 13 Hopkinson, 14 and Krische 15 to deliver functionalized 1-isochromanones. However, the preparation of a structurally similar motif -isochroman -through an oxa-DA reaction is significantly underexplored.…”
Section: Figure 1 Representative Of Biologically Active Isochromansmentioning
confidence: 99%